(untitled) (Academic Journal of Internal Affairs, 2020)
To handle the migration crisis was one the most important questions of the postwar Europe. Forced migration caused by the Second World War had impact even on Hungary. After that the communists took control, borders were closed and migration was under strict state control. The communist party aimed to close the borders and push the migration back. During this period only few decisions have been made at the highest level of the communist party motivated by political ideological reasons, for example refugees from Greece at the end of the forties, or refugees from Chile at the beginning of the seventies. Those people were leftists and – although in reduced circumstances – they got real opportunity to settle down in Hungary. At the end of the eighties, the refugee wave from Romania was motivated by different reasons and features. In order to handle the crisis, caused by the refugee wave, Hungary ratified the Geneva Convention relating to the Status of Refugees.